2022
DOI: 10.1007/s00167-022-06922-7
|View full text |Cite
|
Sign up to set email alerts
|

High recall bias in retrospective assessment of the pediatric International Knee Documentation Committee Questionnaire (Pedi-IKDC) in children with knee pathologies

Abstract: Purpose The increasing incidence of knee injuries among children is well known by sports physicians. Papers dealing with this topic have often collected patient-reported outcomes measures (PROMs) in a retrospective manner; this limitation could lead to a misinterpretation of the results, because pediatric patients might not remember their preoperative conditions adequately. This study aims to evaluate the reliability and the reproducibility of the IKDC pediatric score when administered retrospectively at a 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Due to the retrospective nature of the survey, there is also a possibility of recall bias in parent reporting. For example, studies have shown greater recall bias from participants with poorer outcomes, as well as decreased ability to recall accurately over longer time periods [ 54 ]. As this survey only required parents to recall information and emotions from only a few months prior, this is not likely to have as large of an effect on our study as it would have if the survey was completed further from the start of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the retrospective nature of the survey, there is also a possibility of recall bias in parent reporting. For example, studies have shown greater recall bias from participants with poorer outcomes, as well as decreased ability to recall accurately over longer time periods [ 54 ]. As this survey only required parents to recall information and emotions from only a few months prior, this is not likely to have as large of an effect on our study as it would have if the survey was completed further from the start of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Larger, more gender-diverse samples will be necessary to investigate the sleep experience for non-binary adolescents. Third, our study relied on self-report measures, which are subject to reporter and recall bias (Macchiarola et al, 2022). Speci cally, we recommend that future work assessing the mechanistic role of sleep employ objective measures of sleep (e.g., consumer-grade wearable devices, actigraphy watches, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might consider providing an introductory movie to introduce some difficult terms (e.g., tinnitus, hyperacusis, hearing protection, and speech understanding) and provide information on how to fill out the survey. Moreover, efforts should be made to minimize the recall bias (e.g., asking questions about the last days), as younger is correlated with less recall accuracy [ 18 , 30 ].…”
Section: Discussionmentioning
confidence: 99%